POSITION AND PROTECTION OF ASSOCIATION RIGHTS SECURITY UNIT IN HUMAN RIGHTS PERSPECTIVE ACCORDING TO THE BASIC STATE LAW OF THE REPUBLIC OF INDONESIA YEAR 1945 - Edi Candra; Azmi Azmi; Anne Gunawati (Jurnal Hukum Replik, 2021)
The rights and obligations in the world of labor have been regulated in the labor law, including the right of association which must be given to every worker to associate as stated in Law Number 21 of 2000 concerning Trade Unions / Labor Unions Article 28 and Article 43. In addition, problems arise when the Indonesian National Police Headquarters on behalf of the Indonesian National Police Chief through the Head of the Security Maintenance Agency issues Circular Letter Number; B/194/I/201/Baharkam concerning: Security Guards are Not Members of Trade Unions. In Article 5 of the Circular, it is stated that "in this regard, the security guard is not a member of a trade union and is not allowed to become a member of a trade union organization". Related to this, the writer will discuss about the position of the Security Unit in the perspective of human rights according to the 1945 Constitution of the Republic of Indonesia and how the protection of the right of association for the security unit in the perspective of human rights according to the 1945 Constitution of the Republic of Indonesia. The writing method that the author uses in writing this article is empirical normative, comparing a rule with the situation in the field related to the prohibition for the security unit to associate. The results of the research in this paper are that the regulation of freedom of association rights has two main objectives to be achieved, firstly human rights must be protected as basic rights, secondly there must be guarantees that the rights and freedoms of others can be carried out properly and a form of legal protection against workers in this case the security unit is an effort to fulfill human rights, where one of the important aspects of the application of a rule of law is law enforcement. A new legal instrument is said to be effective if the law can be implemented with sanctions and can be enforced if the law violates it.Keywords: Security Unit, Freedom of Association, Legal Protection